ERGONOMIC REDESIGN OF WORKING TOOLS INCREASES PERFORMANCE OF TRADITIONAL COCONUT OIL MAKERS IN THE DISTRICT OF DAWAN, KLUNGKUNG - Arimbawa, I Made Gede; Adnyana Manuaba, Ida Bagus; Nala, I Gusti Ngurah; Adiputra, Nyoman (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
The business of producing coconut oil in the district of Dawan, Klungkung is oneexample of small-scale home industries in the rural area. The level of working productivityof the oil makers can be categorized as relatively low, as viewed from the aspect of thefollowing indicators: (a) level of working burden, (b) musculoskeletal complaints, (c) levelof fatigue or tiredness, and (d) level of productivity. One factor that causes the lowproductivity is the fact that the working tools used in this industry are non-ergonomicallydesigned such as: (1) tool for peeling off the coconut fibers, (2) tool for taking the coconutflesh, (3) tool for grating the coconut flesh, (4) tool for extracting milk from the watermixedgrated coconut, (5) stove for boiling the coconut milk. Based on the above problemsbackground, it is necessary to make more ergonomic new design or redesign of the toolsthat are used by the coconut oil makers in the district of Dawan in order to increase theirworking performance or productivity.This research was carried out using treatment by subject design by comparing beforeand after treatment involving 22 female subjects selected by simple random method fromall female coconut oil makers in the studied area. Before treatment the research subjectswere asked to make coconut oil as usual with their traditional tools. After an interval ofwashing out period was given, the subjects entered the treatment phase in which they wereasked to make coconut oil by using the tools already redesigned ergonomically. The dataobtained from the research were analyzed by t-paired test at a significance level of 5%.Results of the analysis showed as follows: (1) average of working heart rate beforetreatment was 108.49 ± 0.95 pulse /minute and after treatment 91.92 ± 1.91 pulse /minute,indicating a decrease of workload from moderate to mild one (decrease of working heartrate of 16.59 pulse/minute or 14.69%); (2) average of musculoskeletal complaints beforetreatment was 51.73 ± 1.36 and after treatment 36.79 ± 0.83 (a decrease of 14.94 or26.17%); (3) average of fatigue before treatment was 66.75 ± 3.60 and after treatment49.50 ± 3.28 (a decrease of 17.19 or 25.83%); (4) average of working productivity beforeand after treatment was 35.86 ± 1.09 and 48.66 ± 1.10, respectively (an increase of 12.81 or35.71%). Based on evaluation of investment yield, the NVP value in a five-year period Rp.11.503.431,- > 0, PBP 9.22 months > 0, and RoI 32.54 > 13% (rate of interest commonlyapplied in 2008).It is concluded that redesign of working tools to be more ergonomic has proven to beable to increase the working performance of coconut oil makers and hence worth investing.Novelty of this research is in the positive results related to ergonomic redesigning of thetools for making coconut oil in the district of Dawan, Klungkung by approaches to being systemic, holistic, interdisciplinary, participatory, and appropriate technology usage. Further studies on similar related working issue should focus on the aspects of workingenvironment, especially on how to overcome smoke pollutant in the kitchen area, on moreproper work station and working organization or on that related to production quality of thecoconut oil by generating maximally all the potential already in existence among the localtraditional coconut oil makers.
Keywords: redesign; working tools; ergonomic; working performance